Biomarker testing in non-small cell lung cancer in routine care: Analysis of the first 3, 717 patients in the German prospective, observational, nation-wide CRISP Registry (AIO-TRK-0315). (February 2021) - Griesinger, Frank; Eberhardt, Wilfried; Nusch, Arnd; Reiser, Marcel; Zahn, Mark-Oliver; Maintz, Christoph; Bernhardt, Christiane; Losem, Christoph; Stenzinger, Albrecht; Heukamp, Lukas C.; Büttner, Reinhard; Marschner, Norbert; et al.
Highlights: The CRISP registry collects representative, nationwide data on NSCLC in Germany. CRISP mirrors the treatment and disease trajectory of patients with advanced NSCLC. Biomarker testing rates increased over time, yet are still improvable. 17.7 % of the patients presented with a druggable alteration. Median PFS was longer for patients with a druggable EGFR or ALK alteration. Abstract: Objectives: An increasing number of treatment-determining biomarkers has been identified in non-small cell lung cancer (NSCLC) and molecular testing is recommended to enable optimal individualized treatment. However, data on implementation of these recommendations in the "real-world" setting are scarce. This study presents comprehensive details on the frequency, methodology and results of biomarker testing of advanced NSCLC in Germany. Patients and methods: This analysis included 3, 717 patients with advanced NSCLC (2, 921 non-squamous; 796 squamous), recruited into the CRISP registry at start of systemic therapy by 150 German sites between December 2015 and June 2019. Evaluated were the molecular biomarkers EGFR, ALK, ROS1, BRAF, KRAS, MET, TP53, RET, HER2, as well as expression of PD-L1. Results: In total, 90.5 % of the patients were tested for biomarkers. Testing rates were 92.2 % (non-squamous), 70.7 % (squamous) and increased from 83.2 % in 2015/16 to 94.2% in 2019. Overall testing rates for EGFR, ALK, ROS1, and BRAF were 72.5 %, 74.5 %, 66.1 %, and 53.0 %, respectively (non-squamous). Testing rates for PD-L1 expression were 64.5 % (non-squamous), and 58.5 % (squamous). The most common testing methods were immunohistochemistry (68.5 % non-squamous, 58.3 % squamous), and next-generation sequencing (38.7 % non-squamous, 14.4 % squamous). Reasons for not testing were insufficient tumor material or lack of guideline recommendations (squamous). No alteration was found in 37.8 % (non-squamous), and 57.9 % (squamous), respectively. Most common alterations in non-squamous tumors (all patients/all patients tested for the respective biomarker): KRAS (17.3 %/39.2 %), TP53 (14.1 %/51.4 %), and EGFR (11.0 %/15.1 %); in squamous tumors: TP53 (7.0 %/69.1 %), MET (1.5 %/11.1 %), and EGFR (1.1 %/4.4 %). Median PFS (non-squamous) was 8.7 months (95 % CI 7.4–10.4) with druggable EGFR mutation, and 8.0 months (95 % CI 3.9–9.2) with druggable ALK alterations. Conclusion: Testing rates in Germany are high nationwide and acceptable in international comparison, but still leave out a significant portion of patients, who could potentially benefit. Thus, specific measures are needed to increase implementation.